Turismo e reinvenção de tradições: a relação entre marketing turístico e folclorização da cultura na Estrada Real, Brasil - Carina Amorim Dutra (Confins)
The construction of the imaginary about Minas Gerais is strongly influenced by the mineiro way of life. This folkloric figure is an input for tourism, which, due to “mineiridade”, offers the Estrada Real (ER) to the market. The route is based on the narrative of the gold cycle that built the political identity of Minas Gerais. In the 20th century, took place from the political to the political-economic field, with “mineiridade” becoming a tourist commodity. The ER, an expression of Minas Gerais history, becomes a representative of the “mineiridade”. Through the geo-historical approach, we will discuss the power relations that built this identity appropriation. Would the ER, through “mineiridade”, be able to found new tourist territorialities? The data comes from the route's promotional material and interviews with tourists and the Estrada Real Institute. An identity game combines pairs of opposites since the past adapts to the interests of the present: suspicious, the “mineiro” is welcoming; humble, he can be sophisticated - for tourist interest; charming by provincialism, he is universal. The local and the global are mixed in the facet of a fluid “mineiridade”. A gap between the institutional project, the real territory and the tourist's adhesion to the ER is evident. The efficiency of regional identity discourses is relative.